Therapeutic HDAC inhibition in hypermutant diffuse intrinsic pontine glioma - Alyssa Noll; Carrie Myers; Matthew C. Biery; Michael Meechan; Sophie Tahiri; Asmitha Rajendran; Michael E. Berens; Danyelle Paine; Sara Byron; Jiaming Zhang; Conrad Winter; Fiona Pakiam; et al. (Neoplasia: An International Journal for Oncology Research, 2023)
Constitutional mismatch repair deficiency (CMMRD) is a cancer predisposition syndrome associated with the development of hypermutant pediatric high-grade glioma, and confers a poor prognosis. While therapeutic histone deacetylase (HDAC) inhibition of diffuse intrinsic pontine glioma (DIPG) has been reported; here, we use a clinically relevant biopsy-derived hypermutant DIPG model (PBT-24FH) and a CRISPR-Cas9 induced genetic model to evaluate the efficacy of HDAC inhibition against hypermutant DIPG. We screened PBT-24FH cells for sensitivity to a panel of HDAC inhibitors (HDACis) in vitro, identifying two HDACis associated with low nanomolar IC50s, quisinostat (27 nM) and romidepsin (2 nM). In vivo, quisinostat proved more efficacious, inducing near-complete tumor regression in a PBT-24FH flank model. RNA sequencing revealed significant quisinostat-driven changes in gene expression, including upregulation of neural and pro-inflammatory genes. To validate the observed potency of quisinostat in vivo against additional hypermutant DIPG models, we tested quisinostat in genetically-induced mismatch repair (MMR)-deficient DIPG flank tumors, demonstrating that loss of MMR function increases sensitivity to quisinostat in vivo. Here, we establish the preclinical efficacy of quisinostat against hypermutant DIPG, supporting further investigation of epigenetic targeting of hypermutant pediatric cancers with the potential for clinical translation. These findings support further investigation of HDAC inhibitors against pontine high-grade gliomas, beyond only those with histone mutations, as well as against other hypermutant central nervous system tumors.